Role of Animal Husbandry Nutrition Science on Feed, Food and Environment Safety - Mayulu, Hamdi (Technium BioChemMed, 2023)
Animal protein is an important part of the human diet to support physical activities. The role of livestock as a source of animal protein requires adequate nutrition from feed to be able to produce optimally. The feed must be given in adequate amount of quality and quantity, safe feed (not toxic) is a must, and this cannot be separated from the contribution of animal husbandry nutrition science. Formulation of feed ingredients based on local feed and agro-industrial by-products into complete feeds in ruminant production is a strategy to meet the nutritional needs of ruminants so that they can produce optimally, efficiently, and environmentally friendly which ultimately produces products that are safe for human consumption. The success of this strategy has a greater opportunity through a corporate-based livestock approach, and through this approach, it is expected that the concepts of safe feed, safe food, and safe environment can be realized. Based on this phenomenon, animal husbandry nutrition science has proven its capability to contribute significantly to 1) produce livestock (ruminants) with efficient nutrition; 2) improve food safety and quality of food products originating from livestock for human consumption; 3) improve health status and welfare of livestock; and 4) reduce greenhouse gas emissions and the impact of livestock on environmental security.